A Translation and Literary Analysis of Adebayo Faleti’s Poem: Ojo Ilayefun” - Ayodele Solomon Oyewale (Yoruba Studies Review)
The concept of friendship in the Yorùbá cultural milieu is very germane to their communal life. Suffice to say that there seems to be no human being without, at least, a friend, the major issue usually is how well-grounded such friendship is, especially in times of need. Friendship development among the Yorùbá usually begins during the formative years via social interaction. However, sustaining such friendship through inter-personal relationship, which requires great sacrifices, is the most difficult aspect of it. This essay examines the Yorùbá concept of a mutual acquaintance, as depicted in one of Faleti’s poems titled “Ọjọ Ìláyẹfún.” The essay employs the hermeneutics model to undertake a literary analysis of the poem, which serves as the primary data for the study. By analyzing the representational meanings that are attributed to the concept of friend (òré in Yorùbá, the study shows that the term friendship has many metaphorical meanings in the traditional Yoruba worldview. The study also foregrounds the cultural, metaphorical, and metaphysical meanings of the Yoruba concept of mental imbalance (wèrè) beyond the conventional meaning or common knowledge about it in the Yorùbá socio-cultural milieu. The essay concludes that the Yoruba indigenous system, through several notions and metaphorical expressions about mental malady socially stigmatizes people suffering from such ailment. Mental pictures/images of incurability being rammed the native sub-consciousness, orthodox medicine has proved that it could be managed, suggesting that a lunatic could eventually be reformed, rehabilitated, and re-absorbed into the functionality of society.